COUNTER MEASURES CRIMINAL ACT OF NARCOTICS - Amrullah, Mohammad Arief; Rugebregt, Revency Vania (Pattimura Law Journal, 2017)
Narcotics crimes that are part of organized crime are essentially one of crimes against development and crimes against social welfare that are central to national and international concerns and concerns. It is very reasonable, given the scope and dimensions so vast, that its activities contain features as organized crime, white-collar crime, corporate crime, and transnational crime. In fact, by means of technology can be one form of cyber crime. Based on such characteristics, the impacts and casualties are also very wide for the development and welfare of the community. It can even weaken national resilience.